Bencana Alam Banjir Dan Tanah Lonsor Di Kabupaten Sentani Jayapura Dalam Prespektif Green Criminology - David Hardiago; Rani Fadhila Syafrinaldi (UIR Law Review, 2021)
This article aims to analyze two main problems related to the connection between floods and landslides that occurred in Sentani Jayapura Regency with green criminology discipline as the main approach perspective. This paper also offer projection as a means of prevention of environmental damage that has an impact on the natural disaster. This research uses a multi-method research technique (triangular method), which combines more than one research technique or strategy to study one or several related phenomena. The conclusion, in general, consists of two main parts. First, the connection between flood and landslide natural disasters in Sentani Jayapura Regency with green criminology, lies in the scope of green criminology in relation to factors in factual incidents in the example cases raised. Second, the means of prevention as a projection offer, in outline it consists of several main points. First, restoring the forest area according to its function. Second, conduct a spatial review based on considerations of disaster risk reduction and develop an adaptation scheme at the point of flooding. Third, internalization of land rehabilitation programs in the upstream and middle watersheds (DAS), especially forest areas, into program indications for spatial planning. Fourth, internalization of the soil and water conservation program in the form of Water Drainage (SPA) in agricultural land and settlements to improve regulation so as to reduce the potential for landslides and water accumulation in a short time. Fifth, socialization to the public by providing an understanding of green criminology and the importance of environmental responsibility.